SLISEMAP: Combining Supervised Dimensionality Reduction with Local Explanations - Björklund, Anton; Mäkelä, Jarmo; Puolamäki, Kai (Machine Learning and Knowledge Discovery in Databases, 2023)
We introduce a Python library, called slisemap, that contains a supervised dimensionality reduction method that can be used for global explanation of black box regression or classification models. slisemap takes a data matrix and predictions from a black box model as input, and outputs a (typically) two-dimensional embedding, such that the black box model can be approximated, to a good fidelity, by the same interpretable white box model for points with similar embeddings. The library includes basic visualisation tools and extensive documentation, making it easy to get started and obtain useful insights. The slisemap library is published on GitHub and PyPI under an open source license.